Façade access equipment : structural design, evaluation, and testing (American Society of Civil Engineers, 2015)
This book provides structural engineering guidance regarding the design, evaluation, and testing of permanent anchorages and components that support façade access equipment and fall-arrest systems. Currently this equipment is governed by sections of the Code of Federal Regulations maintained by the U.S. Occupational Safety and Health Administration (OSHA). Many OSHA requirements are not written using terminology that is commonly used by structural engineers, so this book conveys the generally understood meaning of the regulations in terms familiar to structural engineers. --